2009
DOI: 10.1093/pcp/pcp004
|View full text |Cite
|
Sign up to set email alerts
|

Transcript Profiling of an Arabidopsis PSEUDO RESPONSE REGULATOR Arrhythmic Triple Mutant Reveals a Role for the Circadian Clock in Cold Stress Response

Abstract: Arabidopsis PSEUDO RESPONSE REGULATOR (PRR) genes are components of the circadian clock mechanism. In order to understand the scope of genome-wide transcriptional regulation by PRR genes, a comparison survey of gene expression in wild-type Arabidopsis and a prr9-11 prr7-10 prr5-10 triple mutant (d975) using mRNA collected during late daytime was conducted using an Affymetrix ATH-1 GeneChip. The expression of 'night genes' increased and the expression of 'day genes' decreased toward the end of the diurnal light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
250
0
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(270 citation statements)
references
References 66 publications
11
250
0
9
Order By: Relevance
“…These data also suggest that the reduction of CO protein and the long‐hypocotyl phenotype in the prr quadruple mutant are not caused by a general increase in COP1 activity. The long hypocotyl of the prr quadruple mutant may rather be due to impaired circadian‐clock function, causing hyper‐accumulation of transcripts of a clock‐controlled gene, such as PHYTOCHROME INTERACTING FACTOR 4 ( PIF4 ), whose mRNA was increased in abundance in this background and encodes a transcription factor involved in promotion of hypocotyl growth in shade and dark (Fig EV4B; Franklin, 2008; Nakamichi et al , 2009). Accumulation of PIF4 protein requires shade or darkness (Nozue et al , 2007; Leivar et al , 2008; Lorrain et al , 2008), consistent with our data that the long‐hypocotyl phenotype in the prr mutant was observed only under LD and SD conditions, which include periods of darkness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data also suggest that the reduction of CO protein and the long‐hypocotyl phenotype in the prr quadruple mutant are not caused by a general increase in COP1 activity. The long hypocotyl of the prr quadruple mutant may rather be due to impaired circadian‐clock function, causing hyper‐accumulation of transcripts of a clock‐controlled gene, such as PHYTOCHROME INTERACTING FACTOR 4 ( PIF4 ), whose mRNA was increased in abundance in this background and encodes a transcription factor involved in promotion of hypocotyl growth in shade and dark (Fig EV4B; Franklin, 2008; Nakamichi et al , 2009). Accumulation of PIF4 protein requires shade or darkness (Nozue et al , 2007; Leivar et al , 2008; Lorrain et al , 2008), consistent with our data that the long‐hypocotyl phenotype in the prr mutant was observed only under LD and SD conditions, which include periods of darkness.…”
Section: Resultsmentioning
confidence: 99%
“…The long‐hypocotyl phenotype of toc1 prr5 prr7 prr9 mutant might suggest that PRRs prevent the function of COP1 in the established light‐signaling pathway (Fig EV4A). However, this long‐hypocotyl phenotype may be due to increased accumulation of transcripts of the clock‐controlled gene PIF4 , which encodes a transcription factor involved in shade‐ and dark‐mediated promotion of hypocotyl growth (Fig EV4B; Franklin, 2008; Nakamichi et al , 2009). Furthermore, PRRs physically bind to CO (Figs 5 and EV5), further decreasing the possibility that PRRs suppress general COP1 activity or participate in the mechanisms that mediate light‐dependent suppression of COP1 activity, such as promotion of its migration to the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore this triple mutant displayed drought resistance, higher freezing tolerance, as well as upregulation of cold responsive genes. 93 The extensive analysis of the prr9/prr7/prr5 triple mutant provided evidence, for the first time in plants, of a molecular link between adjusting carbon supplies and not through affecting the photosynthesis rate, as suggested by Dodd et al 3 It remains to be seen if this principle also applies to clock mutants that cause a long period and/or starch accumulation.…”
Section: The Circadian Clock Beyond Transcriptional Control: Clock Mumentioning
confidence: 95%
“…PRR5 is strongly induced by cold, and SK12 is moderately upregulated by cold ( Figure 5A). PRR5 is a negative regulator of CBF genes and is partially redundant with PRR7 and PRR9 (Nakamichi et al, 2009). The null allele of prr5 used in this study (see Supplemental Figure 11D online) differed from those reported previously (Nakamichi et al, 2009), and this single mutation was sufficient to display phenotypes such as altered expression of CBF genes and sensitivity to freezing temperatures.…”
Section: Online) Error Bars Indicate the Sd (N = 4 In [B] [C] And mentioning
confidence: 99%
“…PRR5 is a negative regulator of CBF genes and is partially redundant with PRR7 and PRR9 (Nakamichi et al, 2009). The null allele of prr5 used in this study (see Supplemental Figure 11D online) differed from those reported previously (Nakamichi et al, 2009), and this single mutation was sufficient to display phenotypes such as altered expression of CBF genes and sensitivity to freezing temperatures. Mis-spliced transcripts of PRR5 and SK12 in rcf1-1 presumably disrupt the normal function of these two genes, leading to increased induction of CBF genes in rcf1-1 in a similar way to that observed in the prr5 and sk12 mutant plants.…”
Section: Online) Error Bars Indicate the Sd (N = 4 In [B] [C] And mentioning
confidence: 99%